Conformal anomaly from gauge fields without gauge fixing - Falls, Kevin; Morris, Tim R. (Physical review, 2018)
We show how the Weyl anomaly generated by gauge fields, can be computed from manifestly gauge invariant and diffeomorphism invariant exact renormalization group equations, without having to fix the gauge at any stage. Regularization is provided by covariant higher derivatives and by embedding the Maxwell field into a spontaneously broken U(1|1) supergauge theory. We first provide a realization that leaves behind two versions of the original U(1) gauge field, and then construct a manifestly U(1|1) supergauge invariant flow equation which leaves behind only the original Maxwell field in the spontaneously broken regime.
Gesehen am 20.04.2020